Isolasi dan Seleksi Bakteri Kandidat Selulolitik dari Proses Pembuatan Pupuk Organik pada Pengolahan Limbah Peternakan - Akhmad Hidayatulloh; Nadhira Yahdiyani; Lilih Siti Nurhayati (Jurnal Teknologi Hasil Peternakan, 2022)
Cattle farming is one of the livestock business commodities in Indonesia. In the production process, cattle farms produce waste in the form of feces and leftover feed which can be processed in such a way through a decomposition process into organic fertilizer. The rate of the decomposition process is influenced by the existing decomposer microbes. One of the microbes needed in the decomposition process is cellulolytic bacteria. The research was conducted to obtain potential cellulolytic bacterial isolates from the compost which can then be used as a starter in the decomposition process. This research was conducted experimentally with the stages of research including isolation of bacteria from decomposers, the isolates obtained were then reviewed on Nutrient Agar media to produce uniform colonies. Furthermore, screening was carried out to obtain cellulolytic bacteria using NA media added with 1% CMC (Carboxymethyl Cellulose). Based on the results of the study, obtained 7 bacterial isolates that have various cellulolytic indices. The best cellulolytic index was produced by isolates NC-12, NC-17, and NC-16.